2005
DOI: 10.2114/jpa.24.93
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro Patch-clamp Recording Analysis of the Process of Sensory Transmission in the Spinal Cord and Sensory Cortex

Abstract: Following the integration and modification of the sensory inputs in the spinal cord, the information is transmitted to the primary sensory cortex where the integrated information is further processed and perceived. Processing of the sensory information in the spinal cord has been intensively investigated. However, the mechanisms of how the inputs are processed in the cortex are still unclear. To know the correlation of the sensory processing in the dorsal horn and cortex, in vivo and in vitro patch-clamp recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Following the successful application of patch-clamp recording in vivo in other systems (Covey, Kauer, & Casseday, 1996; C. I. Moore & Nelson, 1998), use of whole-cell recording techniques in the nociceptive systems of the spinal cord of the rat in vivo was reported (Furue, Narikawa, Kumamoto, & Yoshimura, 1999; Graham, Brichta, & Callister, 2004; Light & Willcockson, 1999; Weng & Dougherty, 2002; Yoshimura, Doi, Mizuno, Furue, & Katafuchi, 2005). The obvious advantages of this technique include better control over the electrical properties of the neuron, a more robust technique than sharp electrode intracellular recording, the ability to observe single channel activity in the native milieu, and easier control of both intracellular and extracellular medium for drug application.…”
Section: The Neuroscience Of Painmentioning
confidence: 99%
“…Following the successful application of patch-clamp recording in vivo in other systems (Covey, Kauer, & Casseday, 1996; C. I. Moore & Nelson, 1998), use of whole-cell recording techniques in the nociceptive systems of the spinal cord of the rat in vivo was reported (Furue, Narikawa, Kumamoto, & Yoshimura, 1999; Graham, Brichta, & Callister, 2004; Light & Willcockson, 1999; Weng & Dougherty, 2002; Yoshimura, Doi, Mizuno, Furue, & Katafuchi, 2005). The obvious advantages of this technique include better control over the electrical properties of the neuron, a more robust technique than sharp electrode intracellular recording, the ability to observe single channel activity in the native milieu, and easier control of both intracellular and extracellular medium for drug application.…”
Section: The Neuroscience Of Painmentioning
confidence: 99%
“…Previously, Yoshimura et al [42] reported that noxious pinch stimulation near a whisker pad did not produce any significant response in SI neurons located at 100 to 1000 μm from the surface of the cortex in urethane-anesthetized rats. In the present study, only 33% (21/63) of the SI neurons tested (at a depth of 750–900 μm) responded to noxious stimulation applied to the orofacial area.…”
Section: Discussionmentioning
confidence: 99%
“…This in vivo patch-clamp recording technique permits functional analyses of modality-dependent synaptic responses evoked by acupuncture. Therefore, the behavioral changes at the single-cell level can be explained with more certainty [47]. …”
Section: Study Of Acupuncture-induced Changes In the Central Nervomentioning
confidence: 99%